Small business economics of the Lakota Fund on the Native American Indian reservation - David A. Benson; Aaron Lies; Albert A. Okunade; Phanindra V. Wunnava (Institute for the Study of Labor (IZA), 2009)
Poverty rates on Native American Indian reservations are triple the US average. Small business incubation programs, available elsewhere in the US, are sparse on the reservations. Small businesses are potent drivers of US economic growth. Some 25.5 million entrepreneurs generate more than 50% of the GDP, are 26% of the exporters, and create 80% of the total net new job formation. The Small Business Administration (SBA), an independent agency of the federal government created in 1953, maintains and strengthens the nation's economy by aiding, counseling, assisting, and protecting the interests of small businesses and by assisting families and businesses to recover from national disasters. SBA services hardly exist on the Native American Indian Reservations (NAIRs), however. Studies have linked micro entrepreneurial activities to economic growth and poverty reduction. Our study tests the effects of the Lakota Fund (LF), a small business development initiative, on the NAIRs to determine whether SBA-like programs (loans, training, and consulting) can improve economic conditions on the NAIRs. The LF, a private micro loan and business training initiative on the Pine Ridge Reservation in South Dakota, is tested for its effectiveness in generating income. The 1980-2006 annual county-level data (Shannon Co. is 'treatment', Todd Co. is 'control') are a natural experiment; the counties are similar otherwise. Using the real per capita income (RPCI) dependent variable, and controlling for other factors, our regression results indicate that the LF initiative and its duration (intensity) raised RPCI significantly - suggesting the success of a privately funded small business incubation initiative targeted at isolated impoverished groups within the highly developed US economy. Suggestions for future research and program replication ideas are explored.
urn:nbn:de:101:1-20090123110
Keywords: L26; M21; O16; 330; Poverty rates; Small Business Administration; Lakota Fund; life expectancy; public sector; Klein- und Mittelunternehmen; Wirtschaftsförderung; Armutspolitik; Wirkungsanalyse; Indianer; Sterblichkeit; USA